Board characteristics and firm performance: evidence from banking industry in India - Manmeet Kaur; Madhu Vu (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Board of Directors in a firm performs the primary role of internal control mechanism. This Study seeks to understand the relationship between internal governance and performance of banks in India. The research paper investigates the effect of board characteristics (proportion of independent directors, gender diversity, board size, meetings per year and attendance in board meetings) on the firm performance. This paper evaluates the impact of corporate governance mechanisms on bank’s financial performance using panel data for 28 listed banks at National Stock Exchange of India for the period of 2008-2014. Returns on Asset, Return on Equity, Tobin’s Q and Net Interest Income were used as the financial performance indicators. To estimate the relationship among governance and bank performance initially the Study uses Pooled Ordinary Least Square (OLS) Estimation and Generalized Least square (GLS) Estimation. Then a well-developed Generalized Method of Moments (GMM) Estimator is used to investigate the dynamic nature of performance and governance relationship. The Study empirically confirms that two step system GMM approach controls the problem of unobserved heterogeneity and endogeneity as compared to the OLS and GLS approach. The result suggests that banks with small board, boards with female members, and boards that meet more frequently tend to be more efficient and subsequently have a positive impact on performance of banks. The study offers insights to policy makers interested in enhancing the quality of governance of banks in India. In addition, the findings suggest that board characteristics play a vital role in the improvement of corporate governance mechanism for financial institutions. There is a great need to have efficient boards in banks to improve the overall health of the financial institutions and the economic development of the country.